Scaling behaviors of transient noise current in organic field-effect transistors - Choo, K.Y.; Muniandy, S.V.; Chua, C.L.; Woon, K.L. (Elsevier, 2012)
Top-contact and bottom-gate organic field-effect transistors (OFETs) based on poly(3-hexylthiophene), P3HT polymer has been fabricated with thermal treatment condition. Transient noise currents of the OFETs are measured at various source–drain voltages ranging from 0 V to −60 V with respect to a fixed gate voltage of −60 V. The results from conventional power spectral density method are compared with the more robust Detrended Fluctuation Analysis. The latter has been proven to be reliable for fractal signals particularly in the presence of nonstationary effects. Interesting transitions between multiscaling and monoscaling behaviors are observed in the power spectral density as well as the Detrended Fluctuation Analysis plots for different applied source–drain voltage Vds. Uncorrelated white noise characteristics are observed for noise current measured at low Vds, meanwhile 1/f noise-like scaling behaviors are observed at intermediate Vds. At higher Vds, the noise characteristics appeared to be close to Brownian-like power-law behavior. The scaling characteristics of the transient noise current can be related to the charge carrier dynamics. It is also found that large numbers of trap centers are induced when the device is stressed at high applied Vds. The existence of these trap centers would disperse charge carriers, leading to 1/f type noise that could diminish the presence of Brownian noise in a very short time.